IMPACTOS DA PANDEMIA DA COVID-19 SOBRE A PECUÁRIA LEITEIRA NO BRASIL / IMPACTS OF THE COVID-19 PANDEMIC ON DAIRY LIVESTOCK IN BRAZIL - Pizzio, Alex; Polastrini, Alessandra; Xavier Pedroza Filho, Manoel; Souza Ribeiro, Vinicius (Informe GEPEC, 2023)
Este estudo objetivou analisar o cenário nacional da pecuária leiteira antes e durante a pandemia da COVID-19. Foram realizadas pesquisas documental e bibliográfica, bem como avaliação da especialização por meio do Quociente Locacional para os anos 2018, 2019, 2020 e 2021, cuja abrangência se estendeu em todo o território brasileiro. As análises revelaram que a pecuária leiteira nacional não foi fortemente afetada pela pandemia da COVID-19, visto que a produção, o valor da produção e outros aspectos avaliados permaneceram em patamares positivos. No que concerne à especialização dos estados, constatou-se que não houve retrocesso de estados especializados na produção de leite durante os dois anos de pandemia. Resultados similares foram confirmados por estudos realizados em diversos países em todo o mundo, que demonstraram a mesma tendência. Os resultados deste estudo sugerem que pesquisas futuras foquem e investiguem os meios de tornar as cadeias leiteiras mais resilientes. ABSTRACT: This study aimed to analyze the national scenario of dairy farming before and during the COVID-19 pandemic. Documentary and bibliographic research were carried out, as well as an evaluation of the specialization through the Location Quotient for the Years 2018, 2019, 2020 and 2021, whose scope extended throughout the Brazilian territory. The analyzes revealed that national dairy farming was not strongly affected by the COVID-19 pandemic, as production, production value and other aspects evaluated remained at positive levels. Regarding the specialization of the states, it was found that there was no setback of states specializing in milk production during the two years of the pandemic. Similar results were confirmed by studies carried out in several countries around the world, which showed the same trend. The results of this study suggest that future research will focus on and investigate ways to make dairy chains more resilient.